Devolution policy and its implication on watershed restoration in eastern Uganda - Akello, S.; Turyahabwe, N.; Sseguya, H.; Agea, J.G. (African Journal of Rural Developement, 2017)
Whereas decentralisation has received support as an institutional panacea to natural resource management, devolution is seen as an effective solution to local collective action in watershed restoration. Despite conducive institutional and policy environment in Uganda, restoration of Awoja watershed has not been successful. This paper analysed the institutional framework that supports restoration of Awoja watershed. The study was carried out in Ngora district, employing mixed methods. Content analysis results indicated weak inter-sectoral linkages between departments, absence of ordinances and by-laws on watershed restoration as partly reasons for failed restoration. Chi square analysis showed a significant relationship between restoration of vegetation cover and management decision making (P=0.000), community-government relations (P=0.000) and benefit sharing (P=0.002) in Awoja watershed. Therefore restoration efforts will not gain their full potential unless the linkages between sectors, departments, government and the community are strengthened. This framework review gives insight on how devolution can better the governance of Awoja watershed and other similar ecosystems for appropriate restoration.
Keywords: Awoja; Common pool resource; Institutional analysis; Teso sub region; Uganda